Responding to the need for wise use of social-media through legal counseling in the Foster Village of Cikarageman, Bekasi Village - Lubis, Efridani; Intihani, Siti Nur; Fauziah; Riyanto, Slamet; Yoesuf, Juliani Paramitha; Sinta Elviyanti; Zipan; Alizaldi, Annisa Nadialifuzana (Universitas Ahmad Dahlan, 2024)
Currently, all levels of society everywhere can use social media easily. This convenience makes freedom of expression increasingly out of control, and often results in legal problems. Indonesian people who use social media or social media must be wiser in using social media to express freedom of opinion so as not to get caught in criminal cases. Community service (PKM) is carried out in 2 (two) activities, namely: 1) training on the wise use of social media, and 2) e-court socialization (e-court justice). The aim of the activity is to provide training to the community in Cikarageman Village, Bekasi in terms of wise use of social media to avoid legal entanglements and socialization of e-court implementation in court. Activities carried out face-to-face by providing material on the ITE Law, the role of the ITE Law in social media, ways and tips for using social media wisely so as to avoid legal entanglements, examples of cases of using social media which resulted in legal proceedings and providing material on the application of e -court in Court. The activity was attended by representatives from Cikarageman Village units, Bekasi, namely the PKK Unit, BPD Unit, and local residents. During this activity, discussions and consultations were also held regarding legal issues faced by the residents of Cikarageman Village, Bekasi. In this consultation activity, the material provider answers all legal issues faced by residents, both those directly related to the use of social media, the application of e-court in courts and other legal issues, for example land issues, debts, households and judicial processes.